Comparative chloroplast genome analysis of five widespread species (Zanthoxylum L.) and development of molecular markers for their discrimination - Chong Sun; Chong Sun; Huamin Liu; Yuan Guo; Xueqian Fu; Xinxin Zhu; Han Liu; Han Liu; Ning Tang; Zexiong Chen; Yiqing Liu; Yiqing Liu; et al. (Frontiers in Genetics)
BackgroundZanthoxylum L., an important genus in the Rutaceae family, has great edible and medical values. However, the high degree of morphological similarity among Zanthoxylum species and the lack of sufficient chloroplast (cp) genomic resources have greatly impeded germplasm identification and phylogenetic analyses of Zanthoxylum.MethodsHere we assembled cp genomes of five widespread species (Zanthoxylum bungeanum, Z. armatum, Z. nitidum, Z. ailanthoides and Z. piasezkii) in China as a case study, comparative analysis of these assembled cp genomes.ResultsEach of them, ranging from 157,231 to 158,728 bp, has a quadripartite structure. Except for one extra gene in Z. piasezkii, 132 genes were identified in each species, including 87 encode protein genes, 37 transfer ribose nucleic acid (tRNA) genes, and eight ribosomal RNA (rRNA) genes. Substantial variation was observed among these five cp genome sequences in the IR/SC boundary regions. Variation in insertions and deletions were observed in the cp genomes of the five species over three different intervals, and a large number of single-nucleotide polymorphism variants were detected in the rps3-rpl22-rps19 region. Phylogenetic analysis of complete cp genome sequences revealed the evolutionary relationships among 23 Zanthoxylum species (29 samples).ConclusionComparative analysis revealed that rps3-rpl22-rps19 is a highly variable divergent region in Zanthoxylum that could be developed as candidate markers for phylogenetic studies and species identification. This study identified a pair of molecular markers from hypervariable regions that can be used to distinguish between the five Zanthoxylum species and validated their utility. Overall, the results of this study provide new insights into the genetic breeding, germplasm exploration, and phylogeny of Zanthoxylum species.